The Place of Church History in the Rise of Evangelicalism - Schmidt, Darren W. (Historical Papers, 2007)
This article was accidently shortened during the publishing process of Historical Papers 2007. It was, therefore, republished in Historical Papers 2008 in its entirety, and is available in that online edition.